Preventing duplication of digital music file using a new cognitive and constructive learning approach - Hamzah, Hammuzamer Irwan; Low, Tan Jung; Abdul Mutalib, Ariffin (Faculty of Computing, Universiti Teknologi Malaysia, 2016)
A new method is required to prevent duplication when digital musical data are inserted onto the hard disk.Currently, the digital music duplication detection application can detect duplication of digital music records on the hard disk, but unfortunately, duplication still happened. Using these applications, the replicate digital music files can be searched and moved into other folders.The user needs to manually delete these files.This study presents a new approach called the Cognitive and Constructive Learning (CCL) approach to preventing duplication from occurring when a digital music file is inserted onto a personal device.This study reviews and adapts the requirements of the digital music technology, as well as the human recognition and learning concepts. The main objective of this study is to propose a model known as the Digital Music Archiving Model (DMAM) in preventing duplication of the digital music file on a personal device based on the new CCL approach.A comparative analysis is conducted between the DMAM and the existing digital music duplication detection applications.Review by focus group is also sought to assess the most important part of this research work. The results obtained show that the DMAM is capable of preventing duplication of digital music files on a personal device based on the new CCL approach better than the bench marked methods.The hard disk of the personal device can offer extra spaces for digital music records archiving.